Modeling and control of a multi degree of freedom flexible joint manipulator - Akhtaruzzaman, Md.; Akmeliawati, Rini; Teh, Wai Yee (2009)
—The paper describes the model of a two flexible joint manipulator and the development of a nonlinear passivity based control method for that model. For dynamic modeling, the Euler-Language approach is selected to model flexible joint manipulator. Since lightweight materials are employed in the construction of manipulator, the assumption that negligible link deformation no longer applies. A nonlinear passivitybased control method for rigid flexible joint as well as flexible link is proposed here. The main idea of Passivity Based Controller (PBC) is to use energy state of a system to provide stabilization. The PBC is developed to achieve two goals: set point regulation and trajectory tracking. The controller brings the end point from unstable position to a certain stable position. Beside that, the controller are developed to control the position of there end-point in such a way that it tracks the desired trajectory which are tested by simulations.